Memorandum on the Hill coolie papers - Wodehouse, Philip Edmond (Adam Matthew Digital, 1857)
Colonial Office file containing documents concerned with the recruitment of Indian emigrants to work as labourers in the British West Indies, including their possible supply to French colonies